Association of Habitual Physical Activity With the Risk of All-Cause Mortality Among Chinese Adults: A Prospective Cohort Study - Hu, Peng; Zheng, Murui; Huang, Jun; Zhao, Wenjing; Wang, Harry H. X.; Zhang, Xiong; Chen, Yuanyuan; Deng, Hai; Qin, Pengzhe; Liu, Xudong (Frontiers in Public Health, 2022)
Objective: This study was conducted to evaluate the association of the risk of all-cause mortality with habitual physical activity (HPA) and its different domains among Chinese adults. Methods: A total of 11,994 participants from the Guangzhou Heart Study were followed up until 1 January 2020. Information on HPA, including leisure-time physical activity (LTPA) and commute activity, was collected using a modified Global Physical Activity Questionnaire. Individual cause of death was obtained from the National Death Registry of China. Cox proportional hazards regression model was used to estimate hazard ratio (HR) and 95% confidence interval (CI) after adjustment for covariates. Results: During 37,715 person-years of follow-up, 208 deaths (1.73%) were observed. When compared with the highest with the lowest exposure tertiles, HPA and LTPA were associated with 34% (HR: 0.66, 95% CI: 0.46-0.95) and 30% (HR: 0.70, 95% CI: 0.49-0.99) reduced risk of all-cause mortality after adjustment for covariates. Commute activity was not associated with mortality risk. For the specific component of LTPA, we found that every 1 MET-hour/week increment of the housework was associated with a 1% (HR: 0.99, 95% CI: 0.98-0.99) decreased mortality risk, and performing brisk walking/health exercises/Yangko was associated with a 46% reduced mortality risk (HR: 0.54, 95% CI: 0.29-0.99). Conclusion: This study suggests that a higher level of HPA and LTPA was associated with a lower risk of all-cause mortality. Our findings suggest people to perform HPA, especially LTPA, as a strategy for mortality reduction and health promotion.